Clinical Efficacy and Safety of Remdesivir in Moderate to Severe COVID-19 Disease in Patients Hospitalized in ICU - Prakash, Jyoti; Das, B (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Background: The COVID-19 pandemic has had a profound impact on global health and economies, and continues to pose significant challenges worldwide. Among the various drugs approved for treating COVID-19, Remdesivir, a purine nucleoside analogue inhibiting RNA-dependent RNA polymerase, has emerged as a key option in managing moderate-to-severe cases. This study evaluated the clinical efficacy and safety of Remdesivir in hospitalized patients with RT-PCR-confirmed moderate-to-severe COVID-19 disease. Conducted in the ICU of a hospital in Bihar, it provided real-world data on Remdesivir's impact on clinical outcomes, including hospital stay and mortality, particularly among patients with comorbidities. The study shows significant improvements in inflammatory markers post-treatment, highlighting the drug's role in managing the disease. It also adds valuable local data to the global understanding of COVID-19 treatment, guiding healthcare providers in similar settings. Materials and Methods: This was a prospective, observational, cross-sectional study based on data collected from patients. A total of 100 patients with moderate-to-severe COVID-19 (RT-PCR positive) were admitted to the intensive care unit (ICU) of Sri Krishna Medical College and Hospital (SKMCH), Muzaffarpur, Bihar, India were enrolled in the study from 12th August to 11th November 2020. All patients with moderate to severe COVID-19 received an injection of Remdesivir, starting with a 200 mg intravenous (IV) loading dose on Day 1, followed by 100 mg IV daily for the next four days, in conjunction with other standard treatments. Results: Out of 100 patients, 88 patients recovered and were discharged, while 12 patients died. The mean age of patients was 54 ± 16 years with male preponderance (4:1). Mean duration of hospital stay was 10.6 ± 5.4 days. C-reactive protein, D-dimer, ferritin and interleukin-6 decreased significantly after treatment with Remdesivir, with p-value <0.01, as compared to values at the time of admission, without any significant side effects. Conclusion: Early Remdesvir administration demonstrated significant efficacy in moderate to severe COVID-19 patients hospitalized in ICU, reducing time to clinical improvement and mortality rate. It has been shown in previous studies to be of significant use in managing moderate to severe COVID-19 and reducing the mortality rate. As cases of COVID-19 are still rampant in our country it may be used in future practice.